A narrative analysis of the birth stories of early‐age mothers. Issue 6 (28th October 2016) - Carson, Anna; Chabot, Cathy; Greyson, Devon; Shannon, Kate; Duff, Putu; Shoveller, Jean
Abstract: The telling of birth stories (i.e. stories that describe women's experiences of giving birth) is a common and important social practice. Whereas most research on birth narratives reflects the stories of middle‐class, 'adult' women, we examine how the birth stories told by early‐age mothers interconnect with broader narratives regarding social stigma and childbearing at 'too early' an age. Drawing on narrative theory, we analyse in‐depth interviews with 81 mothers (ages 15–24 years) conducted in Greater Vancouver and Prince George, Canada, in 2014–15. Their accounts of giving birth reveal the central importance of birth narratives in their identity formation as young mothers. Participants' narratives illuminated the complex interactions among identity formation, social expectations, and negotiations of social and physical spaces as they narrated their experiences of labour and birth. Through the use of narrative inquiry, we examine the ways in which re‐telling the experience of giving birth serves to situate young mothers in relation to their past and future selves. These personal stories are also told in relation to a meta‐narrative regarding social stigma faced by 'teenage' mothers, as well as the public's 'gaze' on motherhood in general – even within the labour and delivery room.